Experimental Research on Seismic Performance of the Full-Bolted Diaphragm-Through Connection to RCFST. Issue 7 (July 2015) - Wu, Liao; Wang, Xiaodun; Luo, Song; Wang, Xin; Cui, Dongbin; Chen, Zhihua
Available literature has indicated that the diaphragm-trough connection is an ideal rigid connection for H shape steel beam to concrete filled steel tube. In this paper, a new fully bolted diaphragm- through connection was proposed and the seismic performance of this new fully bolted diaphragm-through connection which includes bearing capacity, ductility, energy dissipation capacity and stiffness degradation were investigated. The experimental program and four full-scale connection specimens' quasi-static tests are presented in this paper. Results of the tests indicated that this new connection has a good ductility and energy dissipation capacity, and the bolts sliding can improve seismic performance to a certain degree. The features of safety, reliability and economically of the eccentric connection and the welded diaphragm-through connection also been verified in the tests. In additional, the safety theoretical stress ratio between diaphragm chamfer and beam flange should lower than 0.7 is also been proposed in this paper. The high bearing capacity, good seismic performance and outward shift of the plastic hinge showed that this new connection can meet the seismic design principle of "strong column and weak beam" and "strong connection and weak member".